Lepus arcticus Ross 1819 - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
57. Arctic Hare Lepus arcticus French: Liévre arctique / German: Polarhase / Spanish: Liebre artica Other common names: American Arctic Hare, Canadian Arctic Hare, Labrador Hare, Greenland Hare, Polar Hare Taxonomy. Lepus arcticus Ross, 1819, “Southeast of Cape Bowen” (Possession Bay, Bylot Island, latitude 73°37’N, Canada). Formerly, the three arctic species, L. timidus, L. arcticus and L. othus, were included in L. timidus based on morphological characteristics. This is also supported by genetic analysis of mtDNA, although evidence based only on mtDNA should be treated cautiously. There is also the view that two species exist: L. timidus in the Old World and L. arcticus in Greenland, northern Canada, Alaska, and the Chukchi Peninsula, Russia. Other lagomorph taxonomists consider that L. arcticus is conspecific with L. timidus and distinct from the L. othus. Until conclusive evidence is available, the three species are considered distinct species with L. timidus in the Old World, L. othus in Alaska, and L. arcticus in northern Canada and Greenland. As taxonomists are still trying to clarify the species differentiation in Lepus, the subspecific taxonomy is not elaborated yet. The original descriptions of the subspecies are often not very helpful as they are mostly based on few exterior characteristics and small numbers of individuals. It has been shown that the variability is clinal in more careful investigations. Hence, the distinction in subspecies might be arbitrary and unreasonable. Nine subspecies recognized. Subspecies and Distribution. L.a.arcticusRoss,1819—BaffinI,BylotI,andMelvillePeninsula,NENunavut(NCanada). L.a.andersoniNelson,1934—C&NENorthwestTerritoriesandmostofNunavut(NWCanada). L.a.bangsiiRhoads,1896—NewfoundlandandNEL.a.(ECanada.) L.a.banksicolaManning&Macpherson,1958—BanksI,intheCanadianArcticArchipelago. L.a.groenlandicusRhoads,1896—W,N&NEice-freecoastalregionsofGreenland. L.a.hubbardiHandley,1952—PrincePatrickI,intheCanadianArcticArchipelago. ...